2021
DOI: 10.1097/j.jcrs.0000000000000629
|View full text |Cite
|
Sign up to set email alerts
|

Detection of postlaser vision correction ectasia with a new combined biomechanical index

Abstract: To validate and evaluate the use of a new biomechanical index known as the Corvis biomechanical index-laser vision correction (CBI-LVC) as a method for separating stable post-LVC eyes from post-LVC eyes with ectasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…A recent study has shown that the CBI-LVC is highly sensitive and specific in distinguishing stable from ectatic post-LVC eyes. [ 24 ] The mean ± SD pre-LASIK CBI was 0.29 ± 0.22 and 0.31 ± 0.17 in the Blade and Femto group, respectively, whereas the mean ± SD post-LVC-CBI was 0.07 ± 0.19 and 0.09 ± 0.23 in the Blade and Femto group, respectively, which are within normal ranges suggesting stable corneal biomechanics post-LVC, and thus, no further requirement of treatment. Since both CBI and LVC-CBI follow a different scale, we did not compare pre-op CBI and post-LVC-CBI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the CBI-LVC is highly sensitive and specific in distinguishing stable from ectatic post-LVC eyes. [ 24 ] The mean ± SD pre-LASIK CBI was 0.29 ± 0.22 and 0.31 ± 0.17 in the Blade and Femto group, respectively, whereas the mean ± SD post-LVC-CBI was 0.07 ± 0.19 and 0.09 ± 0.23 in the Blade and Femto group, respectively, which are within normal ranges suggesting stable corneal biomechanics post-LVC, and thus, no further requirement of treatment. Since both CBI and LVC-CBI follow a different scale, we did not compare pre-op CBI and post-LVC-CBI.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, corneal biomechanics showed to play an important role for the diagnosis and management of keratoconus (5)(6)(7)(8)(9) post refractive surgery ectasia (10), cross-linking effect (11), measurement of intraocular pressure (12,13), and glaucoma (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Although linked to pachymetry, its performance appears to be highly independent of pachymetry, as assessed graphically. This result was expected, as the CBI was developed for improving keratoconus diagnosis by combining several indices including the DA, velocity, ARTh, and a stiffness parameter [ 23 , 24 ] Whereas standard indices of the Corvis ST device cannot readily be used for the diagnosis of keratoconus or to demonstrate the effect of CXL in vivo, indices developed in the Vinciguerra screening report—including CBI—allow for a more accurate keratoconus diagnosis compared with standard indices [ 11 , 25 ]. Moreover, the diagnostic ability of the CBI is comparable to that of the Pentacam indices for differentiating normal eyes and eyes with forme fruste keratoconus [ 26 ].…”
Section: Discussionmentioning
confidence: 99%